Reasons to fight: preliminary results on motivations to combat fake news - Wenting Yu; Qing Yan (Information Research: An International Electronic Journal)
Introduction. To encourage the public to combat online fake news and revalue truth, it is important to explore the factors that affect individual intention to combat fake news.